Spontaneous Growth of Perovskite-Derived Oxide over Double Perovskite Surface for Enhancing Cathodic Performance in Protonic Ceramic Fuel Cells - Li, X.; Jin, Z.; Wang, C.; Peng, R.; Zha, Y.; Cao, J.; Ji, Y.; Shao, Zongping (2024)
Robust catalytic materials with high activity and stability play important roles in energy conversion and storage devices such as protonic ceramic fuel cells (PCFCs), in which a favourable cathode should possess high oxygen ion, proton and electron triple conductivities, and superior surface oxygen exchange kinetics. Herein, a thermal-driven self-construction phenomenon in cation-nonstoichiometric Ba1+xGd1-xCo2O6-δ is reported, accordingly developing a new type of nanocomposite, that is, double perovskite BaGdCo2O6-δ (DP-BGCO) anchored by perovskite-derived BaCoO3-δ (P-D-BCO) nanoparticles, which, used as the cathode of PCFCs, demonstrates low area-specific resistances of 0.053 and 0.026 ohm cm−2 respectively at 650 and 700 °C over BaZr0.3Ce0.5Y0.1Yb0.1O3-δ protonic electrolyte and attractive peak power densities of 0.87 (650 °C) and 1.15 W cm−2 (700 °C) with outstanding stability, much superior to the similar cell with single-phase BCO or BGCO cathodes. The synergy between the two components brings the outstanding performance with the mixed oxygen ion and electronic conducting perovskite-derived oxide showing superior catalytic activity for oxygen reduction reaction while the double perovskite provides good bulk protonic conductivity to enlarge reaction sites. Such selective self-construction, well manipulated through the A-site cation stoichiometry engineering, provides a facile way for developing new high-performance electrocatalysts with broad application potential.